Study on medical professionals’ acceptance of and factors influencing drone delivery for medical supplies - Zhao Zhang; Chun-Yan Xiao; Ya Wang; Wan-Cui Song; Jia-Yi Sun; Zhi-Guo Zhang (Frontiers in Public Health)
IntroductionDrone delivery technology provides innovative alternatives for the transportation of medical supplies. Due to their quick reaction, effectiveness, and adaptability, drones can drastically reduce the time it takes to deliver medications, vaccines, and emergency supplies as compared to standard logistics models. However, the real marketing of drone delivery technology has been hampered by medical professionals’ concerns about its stability, safety, and dependability. Medical professionals are the primary users of medical delivery drones, hence, their opinions are crucial for the spread of the technology. To encourage the optimization and real-world use of this technology, it is crucial to methodically investigate the elements influencing medical staff’s approval of drone delivery.MethodsUsing a sample of medical personnel from the emergency department of a large hospital in Chengdu City (N=289), this study conducted regression analyses using a binary logistic model for each of the four categories of medical supplies to identify key factors that can influence medical personnel’s willingness to use drones. We then continued to explore the hierarchical structure and dynamic dependency relationships among the deeper factors of these causes using a Fuzzy-ISM model.ResultsThe study concluded that, in the initial stage, priority should be given to creating a favorable development environment for the project rather than pursuing substantive construction; in the trial operation period, the focus of construction should be on strengthening infrastructure and improving professional staffing; in the scale-up stage, the focus of attention should be on cost reduction, improving distribution efficiency, improving project safety, and optimizing the way of managing and operating the project.DiscussionThese improvements will be more conducive to increasing the willingness of medical workers to use drones to distribute medical materials and more conducive also to the early realization of regular distribution of medical materials by drones.